A novel 96-microwell-based high-throughput spectrophotometric assay for pharmaceutical quality control of crizotinib, a novel potent drug for the treatment of non-small cell lung cancer - Tanveer Ahmed Wani; Ibrahim Ali Darwish (Universidade de São Paulo, 2015)
This study describes the development and validation of a novel 96-microwell-based high throughput spectrophotometric assay for pharmaceutical quality control of crizotinib (CZT), a novel drug for the treatment of non-small cell lung cancer. We examined the reaction between CZT and 1,2-naphthoquinone-4-sulphonate, a chromogenic reagent. A red-colored product showing a maximum absorption peak (λmax) at 490 nm was produced in an alkaline medium (pH 9). We examined stoichiometry of the reaction and postulated the reaction mechanism. To our knowledge, this is the first study to describe a color-developing reaction for the proposed assay. The reaction was performed in a 96-microwell plate, and the absorbance of the colored product was measured using an absorbance reader at 490 nm. Under optimized reaction conditions, Beer's law, which shows a correlation between absorbance and CZT concentration, was obeyed in the range of 4-50 µg/well with an appropriate correlation coefficient (0.999). The limits of detection and quantification were 1.73 and 5.23 µg/well, respectively. The assay showed high precision and accuracy. The proposed assay was applied successfully for the determination of CZT in capsules. Thus, the assay proposed in this study is practical and valuable for routine application in pharmaceutical quality control laboratories.